Ruddlesden–Popper Perovskites: Energetics and Energy Loss in 2D Ruddlesden–Popper Perovskite Solar Cells (Adv. Energy Mater. 23/2020). Issue 23 (16th June 2020) - Yang, Jianming; Xiong, Shaobing; Song, Jingnan; Wu, Hongbo; Zeng, Yihan; Lu, Linyang; Shen, Kongchao; Hao, Tianyu; Ma, Zaifei; Liu, Feng; Duan, Chungang; Fahlman, Mats; et al.
Abstract : In article number 2000687, Qinye Bao and co‐workers systematically investigate the energetics and energy loss in 2D Ruddlesden‐Popper perovskite (RPP) solar cells. The crucial scenario found at the 2D RPP/electron transport layer interface is that the potential gradient across ligands promotes separation of the photogenerated carrier, with electrons transferring from the perovskite crystal to the electron transport layer.